Slapping the table in amazement : a Ming Dynasty story collection - Ling, Mengchu, 1580-1644 (Classics of Chinese thought., 2018)
"Slapping the table in amazement is the unabridged English translation of the famous story collection Pai an jingqi by Ling Mengchu (1580-1644), originally published in 1628. The forty lively stories gathered here present a broad picture of traditional Chinese society and include characters from all social levels. We learn of their joys and sorrows, their views about life and death, and their visions of the underworld and the supernatural. Ling was a connoisseur of popular literature and a seminal figure in the development of Chinese literature in the vernacular, which paved the way for the late-imperial Chinese novel. Slapping the table in amazement includes translations of verse and prologue stories as well as marginal and interlinear comments"--